Financial inclusion in Peru: Appraisal and perspectives - Toledo Concha, Emerson (2023)
Financial inclusion is a relevant matter that is constantly being looked upon, given its influence in reducing poverty and enabling the low-income population to access financial products and services, thus improving their living condition. This research aims to analyze the evolution of financial inclusion in Peru during the last seven years (2016-2022);also, it takes into consideration information from secondary source databases, such as reports from the World Bank, the Superintendencia de Banca y Seguros, and the Banco Central de Reserva del Perú. The method used has a descriptive and explanatory design. The findings of the research provide evidence that 56% of the Peruvian population has access to financial services (64% in urban areas and 31% in rural areas), which falls below the goal of 75% set by the Peruvian government. This gap can be attributed to customer service costs, including in-person service or adequate infrastructure for better service (access limitations), and poor financial education (limiting broader usage).